Perception of primary prevention concept by school club educators - Citterbergová, Gabriela; Novocký, Michal (e-Pedagogium, 2018)
In this paper, we present the results of research that focused on finding how school clubs' educators perceive a primary prevention concept. We used our originally designed semantic differential and submited the obtained data to exploration factor analysis through which we identified two factors. The reliability of the research tool was verified by the use of Cronbach alpha value (the dimension of energy α = 0,86; the dimension of evaluation α = 0,88) which indicated good reliability of assembled dimensions. A statistically significant positive relationship has been demonstrated between the length of educators' practice and the perception of the primary prevention concept in both dimensions (p-value = 0,000; rs = 0,378; 0,370). The indirect dependence between the highest achieved education of educators and the perception of primary prevention was not confirmed (p-value = 0,349; 0,421).
Keywords: primary prevention; professional standard; problem behavior; school club; educator